Pengujian Instrumen Pendeteksi Kelainan Ritme Jantung Menggunakan Data Fisiologi MIT-BIH - M. S. Hendriyawan A.; Indah Soesanti; Litasari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
MIT-BIH database provides authentic ECG signal data that can be used as a source to test the system with varied type of disorders and duration of observation. MIT-BIH ECG signals are converted to analog signals using 11-bit DAC with 360 Hz frequency conversion. Microcontroller converts the analog signals from the output of the generator using an internal 10-bit ADC with a sampling frequency of 200 Hz. Cardiac abnormalities are then analysed based on data sampling. Abnormal heart rhythms are identified using R peak parameter. By measuring the interval between R peaks, the number of beats per minute (bpm) and the interval variation between R peaks can measured to determine abnormal heart rhythms. Results show that DAC output obtains error range from 6.72 milivolt to 14.58 milivolt, whereas ADC output obtains error range from 1 bit to 2 bit. Statistically, test results show significance values from ideal values are greater than α = 0,05 meaning that there is no significant difference between measured R-R intervals with the original R-R intervals by 95% confidence level. The test method successfully detects multiple type of heart rhythms with category: normal, bradycardia, tachycardia, and irregular.